Fear of cancer recurrence: A qualitative systematic review and meta-synthesis of patients' experiences. (March 2019) - Almeida, Susana N.; Elliott, Robert; Silva, Eunice R.; Sales, Célia M.D.
Abstract: Fear of cancer recurrence (FCR) is a significant issue for most cancer survivors, with nearly half of cancer survivors reporting it at moderate to high levels of intensity. We aimed to further explore the experience of having FCR from the point of view of patients by systematically reviewing qualitative studies. Following PRISMA guidelines, 87 qualitative studies were selected. All participants' quotes about FRC were extracted, then analysed using a conceptual framework based on the emotion-focused therapy theory of emotion schemes, which consist of experienced/implicit emotions, along with perceptual-situational, bodily-expressive, symbolic-conceptual and motivational-behavioral elements. According to participant descriptions, FCR was found to be an intense, difficult, multi-dimensional experience. Considering the diversity of experiences identified, it is useful to look at FCR as an emotional experience that extends along a continuum of adaptive and maladaptive responses. For some participants, FCR was described in trauma-like terms, including forms of re-experiencing, avoidance, negative thoughts and feelings, and arousal or reactivity related to cancer-related triggers or memories. Vivid metaphors expressing vulnerability and conflict also reflect the strong impact of FCR in patients' lives and can help therapists empathize with their clients. Highlights: Qualitative data complement quantitative findings and can expand our current knowledge about fear of cancer recurrence. FCR is described as a complex experience involving emotional, perceptual, conceptual, bodily and behavioral dimensions. Survivors often refer FCR when speaking of their cancer experience, ranging on a continuum from adaptive to maladaptive. Vivid metaphors of conflict and vulnerability emphasizing fragility and helplessness are commonly used by survivors. Psychotherapists may use our results as a kind of map of the aspects and varieties of FCR experience.